THE CHARACTERISTIC USE OF SATIRE IN THE WORK OF MUHAMMAD AMINKHUJA MUKIMIY (Euro-Asia Conferences, 2021)
By the 19th century, in our literature a new direction, a largegeneration began to grow. If their first representatives were Munis,Ogahi, Almaiy, then their next representatives are Ibrat, Mukimiy,Furqat, Zavkiy. These are well-known representatives of Uzbekliterature of the period of national Renaissance. The purpose of thisarticle is to study the heritage of creative works of Mavlene Mukimiy.